Stenotrophomonas maltophilia promotes wheat growth by enhancing nutrient assimilation and rhizosphere microbiota modulation - Sharma, Pinki; Pandey, Rajesh; Chauhan, Nar Singh (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundStenotrophomonas maltophilia has gained considerable attention for its biocontrol and biofertilizer potential in promoting plant growth. It could be employed to enhance wheat yield to ensure food security for the growing population. However, its biofertilizer potential in field conditions and its impact on wheat rhizosphere microbiota must be assessed before its employment in agriculture practices to increase wheat production.MethodsWe have assessed the role of S. maltophilia on wheat seed germination, plant growth parameters, and crop yield in the field conditions. Additionally, wheat rhizosphere microbiota was explored to assess the impact of seed pretreatment with S. maltophilia on the wheat rhizosphere microbiota.Results and discussionS. maltophilia strains BCM and BCM_F demonstrated superior antifungal activity, indicating their biocontrol potential. Seed pretreatment with these strains promoted nitrogen fixation and phosphate solubilization in the wheat rhizosphere showcasing biofertilizer potential. Uniquely identified OTUs in the rhizosphere microbiota of treated groups and microbial community dynamics, particularly at Feeks 3.0 and 6, indicated S. maltophilia-induced microbiota restructuring. The abundance of S. maltophilia 16S rRNA gene sequences at different Feeks treated with microbial indicates its stability across different plant growth stages. Their rhizospheric presence also impacted plant health indicators, including improved sugar and nitrite concentrations and significantly enhanced crop yield (P < 0.05). Enhanced growth parameters and better crop yield in S. maltophilia pre-inoculated seeds in field conditions indicated their potential to offer a sustainable alternative to enhance wheat production.ConclusionThe present study highlighted the biofertilizer and biocontrol potential of S. maltophilia strains BCM and BCM_F in supporting sustainable agricultural practices.